Adult onset progressive cribriform and zosteriform hyperpigmentation: a rare presentation - Aastha Gupta; Prekshi Bansal; Pooja Arora (Wolters Kluwer Medknow Publications, 2020)
Progressive cribriform and zosteriform hyperpigmentation (PCZH) is an uncommon pigmentary disorder characterized by the presence of asymptomatic cribriform brown macules involving a dermatome. Most cases of PCZH present in the second decade of life with gradual extension and absence of systemic involvement. Though the lesions of PCZH are usually localized, multiple lesions may be seen in some cases. We report a rare case of a 50 year old female with adult onset of this disease in fifth decade with extensive involvement of skin along multiple dermatomes.